Le Nouvel ordre mondial : Forces sous-jacentes et résultats - Rosenau, James (Études internationales, 1992)
Although much remains the same in world politics despite claims that a new global order has emerged out of the rubble of the Cold War, there is a level at which the emergence of a new order can be discerned. If one probes beneath the outcomes of international affairs and focuses on their underpinnings, it is possible to trace the utlines of new foundations of global politics. This new world order is depicted in terms of three basic parameters that bind the global System, each of which is posited as undergoing profound and enduring transformation. At the micro level the analytic skills of individuals everywhere are conceived to have undergone extensive expansion. At the macro level of systemic structure the transformation involves the bifurcation of world politics into a state-centric world and a multi-centric world, neither of which is predominant and both of which are responsive to the other. At the macro-micro level, which links individuals to their macro collectivities, transformation is seen to have occurred in authority relations, with the dynamics of change having moved authority structures from being in place to being in crisis. While these fundamental transformations are seen as fostering endless tensions between the centralizing and decentralizing forces at work in the world, the resulting turbulence is not viewed as amounting to disorder. Rather, the emergent global order is viewed as encouraging the institutionalization of the tensions, the outcome of which is readily discernible in present day relations among the states analyzed in this symposium.